Animals and People in the Netherlands' Past: >50 Years of Archaeozoology in the Netherlands. (19th November 2019) - Çakirlar, Canan; van den Hurk, Youri; van der Jagt, Inge; van Amerongen, Yvonne; Bakker, Jan; Breider, Rianne; van Dijk, Joyce; Esser, Kinie; Groot, Maaike; de Jong, Theo; Kootker, Lisette; Steenhuisen, Frits; et al.
More than fifty years ago, Anneke T. Clason published the first English-language archaeozoological study on Dutch faunal assemblages. Inspired by the anniversary of this landmark publication, this paper presents a status overview of Dutch archaeozoology organized in twelve themes (e.g. rituals, Mesolithic-Neolithic transition, medieval period). The paper also discusses the common methods applied in Dutch archaeozoology, and includes extensive supplementary material that summarizes data from gray literature in Dutch. Our aim is to provide a guide to archaeozoological questions pertaining to the Netherlands and open a window for researchers working outside the Netherlands to the highly active world of Dutch archaeozoology.